تأثير جائحة كورونا على تنفيذ الالتزامات التعاقدية - رفيق حراثي (My University, 2022)
Abstract: At the time of the spread of the Coronavirus around the world, the issue of paying responsibility for the foreign cause and in particular force majeure and emergency conditions is, according to our opinion, a matter of importance due to the problems that it may raise in resolving disputes before the courts, especially in the area of paying responsibility and evading The implementation of the obligations imposed on the debtor as it affects the implementation of the contractual obligations, it is a reason that does not result in just a difficulty in implementing the contract but rather an imbalance in the contract that may lead to an absolute impossibility in its implementation. Perhaps determining the impact of the spread of the Coronavirus on resolving disputes that may arise because of the delay or failure to implement legal and contractual obligations and the excuse for the foreign cause; It is not an easy matter for the legislation not to develop a specific legal concept, which merely mentioned cases of foreign cause, in addition to the ambiguity on the other hand that surrounds some articles that differentiate between force majeure and the theory of circumstances. ......................... الملخص في زمن إنتشار فيروس كورونا عبر العالم يعد موضوع تنفيذ الإلتزام التعاقدي أي دفع المسؤولية العقدية بالسبب الأجنبي، وعلى الخصوص القوة القاهرة والظروف الطارئة ، حسب رأينا موضوع على قدر من الأهمية نظراً للإشكاليات التي قد يثيرها في حل النزاعات المطروحة أمام المحاكم، خاصة في مجال دفع المسؤولية و التملص من تنفيذ الإلتزامات المفروضة على المدين إذ تؤثر على تنفيذ الإلتزامات التعاقدية ، فهي سبب لا يترتب عليه مجرد صعوبة في تنفيذ العقد بل إختلال في توازن العقد قد يؤدي إلى إستحالة مطلقة في تنفيذه. لعل تحديد أثر إنتشار فيروس كورونا على حل النزاعات التي قد تنشأ بسبب التأخر أو عدم تنفيذ الإلتزامات القانونية والتعاقدية والتحجج بالسبب الأجنبي ، ليس بالأمر السهل أمام عدم وضع التشريع لمفهوم قانوني محدد، والذي إكتفى فقط بذكر حالات السبب الأجنبي ، إضافة إلى الغموض من جهة أخرى الذي يكتنف بعض المواد تفرق بين القوة القاهرة ونظرية الظروف الطارئة .